The effect of topical latanoprost on corneal clarity; 1-year prospective study†. (3rd July 2019) - Sen, Emine; Inanc, Merve; Elgin, Ufuk
Abstract: Purpose: Quantitatively investigate the effects of topical latanoprost on the corneal optical density parameters by using Scheimpflug system. Materials and methods: New cases of primary open-angle glaucoma treated with topical latanoprost as first-line treatment were enrolled in this prospective study. Corneal densitometry measurements obtained with the Scheimpflug system (Pentacam; Oculus, HR) at baseline and 1st, 3rd, 12th months after topical latanoprost treatment. For densitometry analysis, the 12-mm diameter area of the cornea was subdivided into 4 concentric radial zones and also into anterior, central, and posterior layers based on corneal depth. Pre and post-treatment values were compared statistically by a paired sample t -test. Results: The mean age of 18 female (66.7%) and 9 male (33.3%), totally 27 cases were 59.48 ± 10.1 years. There was no statistically significant difference between pretreatment and 1st-month post-treatment corneal densitometry values in all regions ( p > 0.05 for all). Corneal densitometry values began to decline at 3rd month after treatment. The decrease continued until the 12th month of the beginning of the treatment and was significant in all zones except 2–6 mm of the anterior and central zones ( p = 0.23, p = 0.08, respectively). Conclusion: Long-term administration of topical latanoprost may cause decrease in corneal densitometry measurements. Further prospective studies with a longer follow-up period are required to clarify the relationship between prostaglandin analogues and their effects on the cornea transparency.